User Interface and Interaction Design Considerations for Collaborative Learning Using Augmented Reality Learning Object - Makina, T.; Salam , S. (2011)
Abstract. Most education is too often about teaching and not enough about learning. It is because students are forced to take whatever it is given to them without considering what they think about it, in other words, they passively take the given knowledge. This paper presents early investigation about interface and interaction design considerations for effective collaborative learning by taking account individual learning preferences and collaborative learning characteristics of engineering students. In our investigation, we follow Felder Silverman Learning Style Model and conducted a test measured using Index Learning Style. As a result, we discovered that engineering students tend to be active, sensory, visual, and sequential. Therefore, we implement augmented reality views to satisfy students’ learning preferences toward content presentation (visual learner). It is also because augmented reality can give rich information toward real objects/environment. For collaborative characteristics, we studied past research on collaborative learning regarding its characteristics that affects learning effectiveness. Besides, our proposed design also considered the user interface principle which provides a guidance to effectively implement our consideration into an interface.